Pembelajaran On Line Di Perguruan Tinggi: Analisis Hambatan Komunikasi - Nuzuli, Ahmad Khairul; Astria, Kadek Kiki (BINA' AL-UMMAH, 2021)
The spread of the corona virus 19 in the last two years has had an impact on the learning process at AMIKOM University Yogyakarta. The learning process that was previously carried out face-to-face in the class rooms, must be changed by using technological devices that do not require direct contact between lecturers and students. However, online learning actually gets pros and cons in the community, even from lecturers and students. So the purpose of this study is to see the communication barriers between lecturers and students in the online learning process at AMIKOM University Yogyakarta. The sample of this study involved 3 students and 3 lecturers as resource persons. By using the three groove model simultaneously; data reduction, data presentation, and drawing conclusions/verification obtained findings showing that there are three main obstacles, namely: technical, psychological, and semantic.